(3SdSdI GdSGOI GdNdhJjI hGdHgLI GdSfjIs
(3ChdgG (B:s
(3GdMeO ddg GdgGOi dSHjd CMHGHg s
(3BNQgG (B:s
(3hSde JSdjekG OGFekG Edi jhe GdOjf , hGdMeO ddg QH GdYGdejf s
(3GdeNWhW ai SHY hQbGJ GdUbJ HHYVgG GdHYV ai Tcd YehOis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B231 s
Keywords: (3GdJGQjNs